Effectiveness of a blended (distance and in-person) simulation education program on advanced cardiac life support for nursing students using the PARTNER model - Miyoung Kang; Eunju Lee (BMC Nursing)
Abstract Background The incidence of acute cardiac arrest is increasing and is directly linked to patient survival, highlighting the critical role of nurses. Advanced nursing skills for cardiac arrest patients, such as self-directed pre-learning applied to various clinical situations, require a systematic blended learning approach to integrate knowledge and enhance clinical performance through face-to-face practice. The purpose of this study is to evaluate the effectiveness of a blended simulation education program for Advanced Cardiac Life Support (ACLS) using the PARTNER model. Methods A nonequivalent control group pretest-posttest design with a time-lagged approach was used to collect data from 34 third-year nursing students. The experimental group(n = 17) received a 480-minute blended simulation education program based on the PARTNER model and flipped learning, while the control group(n = 17) participated in a 480-minute traditional simulation education program. Results The study found that knowledge, confidence, performance in advanced cardiac life support, and clinical performance ability were effectively enhanced, although no significant effect was observed in learning satisfaction. Conclusions The program provides a new direction in applying blended simulation using the PARTNER model for advanced cardiac life support nursing education, ultimately contributing to the training of nurses competent in advanced cardiac life support.